The importance of physical fitness for pencak silat athletes: Home-based weight training tabata and circuit can it work? - Patah, Ihsan Abdul; Jumareng, Hasanuddin; Setiawan, Edi; Aryani, Mela; Gani, Ruslan Abdul (UIR Press, 2021)
During the Covid-19 pandemic, pencak silat athletes experienced difficulty improving physical fitness because training could not be done together with a coach, so their physical fitness decreased significantly. This study aimed to test Tabata and Circuit's effectiveness to improve female Pencak silat athletes' physical fitness. This research was quantitative with experimental methods. The subject of this research consisted of Female Pencak silat athletes with low physical fitness levels (n=20). All subjects were randomly allocated to experiment I of the Tabata weight training (TWT) (n = 10) and experiment II of the Circuit weight training (CWT) (n = 10). The results showed that the physical training such as arm muscle strength (t= 11.00; P<0.05), leg muscle strength (t= 7.900; P<0.05), muscle endurance (t= 6.014; P<0.05), flexibility (t= 10.34; P<0.05), endurance VO2max (t= 17.39; P<0.05) and power (t= 19.20; P<0.05), increased significantly due to the intervention of Tabata weight training. A similar increase occurred in Circuit weight training, physical fitness components, such as arm muscle strength (t= 4.910; P<0.05), leg muscle strength (t= 12.230; P<0.05), muscle endurance (t= 4.792; P<0.05), flexibility (t= 6.107; P<0.05), endurance VO2max (t= 5.533; P<0.05) and power (t= 5.982; P<0.05) increased significantly. Home-based weight training between Tabata and Circuit positively improved the physical fitness of female Pencak silat athletes. This research contributes knowledge in coaching so that lecturers and coaches can use it to improve aspects of athlete's physical fitness.